2021
DOI: 10.3390/s21237897
|View full text |Cite
|
Sign up to set email alerts
|

Using Sensorized Gloves and Dimensional Reduction for Hand Function Assessment of Patients with Osteoarthritis

Abstract: Sensorized gloves allow the measurement of all hand kinematics that are essential for daily functionality. However, they are scarcely used by clinicians, mainly because of the difficulty of analyzing all joint angles simultaneously. This study aims to render this analysis easier in order to enable the applicability of the early detection of hand osteoarthritis (HOA) and the identification of indicators of dysfunction. Dimensional reduction was used to compare kinematics (16 angles) of HOA patients and healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…We did not investigate the wrist sensors and the palm arch has shown to be difficult to calibrate. Even though the findings in this work need to be confirmed for arthritis patients as well, it already shows that using the CyberGlove III for objective hand monitoring of healthy subjects is feasible, supporting previous findings ( [2], [6], [8], [11], [12], [22]). Furthermore, the CyberGlove III was already used to discriminate between healthy individual and patients suffering from osteoarthritis with an accuracy of 80 % [8].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We did not investigate the wrist sensors and the palm arch has shown to be difficult to calibrate. Even though the findings in this work need to be confirmed for arthritis patients as well, it already shows that using the CyberGlove III for objective hand monitoring of healthy subjects is feasible, supporting previous findings ( [2], [6], [8], [11], [12], [22]). Furthermore, the CyberGlove III was already used to discriminate between healthy individual and patients suffering from osteoarthritis with an accuracy of 80 % [8].…”
Section: Discussionsupporting
confidence: 86%
“…It was shown that hands should be at least 184 mm long to record DIP joint angles properly [7]. The DIP joint angles are often either not analyzed or not even recorded by using the 18 sensor version of the CyberGlove, due to the difficulties to obtain high quality and reliable measurements [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data employed in this work correspond to experiments from two previous studies [11,24]. The AROM and FROM data, aggregated in [11], are herein provided per subject in the appendices (see Tables A1 to A4).…”
Section: Methodsmentioning
confidence: 99%
“…The present study aims to examine the idea of using ROM as an early indicator of the presence of HOA by performing a linear discriminant analysis with the ROM of those joints that significantly differed to look for a discriminant function capable of detecting HOA in different stages. We successfully tested a linear discriminant analysis to detect HOA in a previous study [24], but we used the kinematic reduced variables obtained from a principal component analysis of hand kinematics while performing the Sollerman hand function test (SHFT) tasks. Although the results were good, the complexity of the technique may hinder its use in clinics.…”
Section: Introductionmentioning
confidence: 99%